The Use of Contextual Learning Approach to Improve Elementary School Students' Understanding of Science Concepts and Social Awareness - Sahlan; Zetra Hainul Putra; Neni Hermita (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
Contextual learning connects instructional content with real-life experiences, promotes active participation, and fosters social interaction among students. This study aimed to analyze the effect of a contextual learning approach on elementary school students’ understanding of science concepts and social awareness. The research employed a quasi-experimental design conducted at an elementary school in Pekanbaru, involving two classes: an experimental class taught using the contextual approach and a control class taught using conventional methods. Data were collected through science concept understanding tests and social awareness questionnaires and analyzed using descriptive and inferential statistics. The t-test results indicated that the significance values of post-test scores for both science concept understanding and social awareness were less than α = 0.05, leading to the rejection of H₀. This demonstrates a significant difference between the experimental and control classes at the 95% confidence level. Further analysis using N-gain scores showed that the experimental class achieved higher improvement in both science concept understanding and social awareness compared to the control class. These findings indicate that the contextual learning approach has a positive and significant influence on students’ conceptual understanding and social awareness.